Local Residents' and Tourists' Attitudes Towards Tourism Development at Patong Beach, Phuket, Thailand - Ketmuang, Srirat (2006)
Tourism development has brought about both the positive and negative impacts to the local communities and to the environment. The acceptance among the residents and tourists may be varied; the acceptance among the domestic tourists and foreign may also be varied. The main objective of the study was to determine the attitudes, as measured by the perceptions, of the local residents, domestic tourists, and foreign tourists on impacts of tourism development in the Patong Beach area of Phuket. Data for the study was collected through clustered sample surveys of the residents and tourists in the Patong Beach area. To ensure consistencies, the secondary information was gathered from various agencies and authorities. A descriptive analysis and a multiple regression analysis were used to determine the results. It was found that the respondents were highly aware of the impacts of the development; the perceptions of the local residents were consistent to previous studies; the residents were divided between the economic impacts and environmental pollution of the industry. They were of the opinion that the enforcement of the laws and regulations must be tightened up to eliminate the problems resulting from the development of the tourism industry. The tourists were also concerned of the impacts on the youths relating to prostitution and crime activities. The tourists believed that education would be the most effective way of overcoming the problems relating to the younger generation. Generally the respondents agreed with the types of policies adopted by the authorities concerned.